Overlapping demyelinating syndromes and anti-N-methyl-D-aspartate receptor encephalitis - Titulaer, Maarten J.; Höftberger, Romana; Iizuka, Takahiro; Leypoldt, Frank; McCracken, Lindsey; Cellucci, Tania; Benson, Leslie A.; Shu, Huidy; Irioka, Takashi; Hirano, Makito; Singh, Gagandeep; Cobo Calvo, Alvaro; et al. (Annals of neurology, 2014)
Objective To report the clinical, radiological, and immunological association of demyelinating disorders with anti–N‐methyl‐D‐aspartate receptor (NMDAR) encephalitis. Methods Clinical and radiological analysis was done of a cohort of 691 patients with anti‐NMDAR encephalitis. Determination of antibodies to NMDAR, aquaporin‐4 (AQP4), and myelin oligodendrocyte glycoprotein (MOG) was performed using brain immunohistochemistry and cell‐based assays. Results Twenty‐three of 691 patients with anti‐NMDAR encephalitis had prominent magnetic resonance imaging (MRI) and/or clinical features of demyelination. Group 1 included 12 patients in whom anti‐NMDAR encephalitis was preceded or followed by independent episodes of neuromyelitis optica (NMO) spectrum disorder (5 cases, 4 anti‐AQP4 positive) or brainstem or multifocal demyelinating syndromes (7 cases, all anti‐MOG positive). Group 2 included 11 patients in whom anti‐NMDAR encephalitis occurred simultaneously with MRI and symptoms compatible with demyelination (5 AQ4 positive, 2 MOG positive). Group 3 (136 controls) included 50 randomly selected patients with typical anti‐NMDAR encephalitis, 56 with NMO, and 30 with multiple sclerosis; NMDAR antibodies were detected only in the 50 anti‐NMDAR patients, MOG antibodies in 3 of 50 anti‐NMDAR and 1 of 56 NMO patients, and AQP4 antibodies in 48 of 56 NMO and 1 of 50 anti‐NMDAR patients (p < 0.0001 for all comparisons with Groups 1 and 2). Most patients improved with immunotherapy, but compared with anti‐NMDAR encephalitis the demyelinating episodes required more intensive therapy and resulted in more residual deficits. Only 1 of 23 NMDAR patients with signs of demyelination had ovarian teratoma compared with 18 of 50 anti‐NMDAR controls (p = 0.011). Interpretation Patients with anti‐NMDAR encephalitis may develop concurrent or separate episodes of demyelinating disorders, and conversely patients with NMO or demyelinating disorders with atypical symptoms (eg, dyskinesias, psychosis) may have anti‐NMDAR encephalitis. Ann Neurol 2014;75:411–428